Dual-task assessment of a sporting skill: influence of task complexity and relationship with competitive performances - Gabbett, T. J.; Abernethy, B. (Journal of Sports Sciences, 2012)
We investigated the effect of increases in task complexity on the dual-task draw-and-pass performance of professional rugby league players. Moreover, we determined the relationship between dual-task draw-and-pass proficiency measured in isolation and draw-and-pass performances as they occurred in actual competitive matches. In Study 1, 12 rugby league players performed 2-on-1 and 3-on-2 attacking drills under single (primary skill) and dual-task (primary skill performed in conjunction with secondary-task) conditions. Reductions in draw-and-pass performance occurred when task complexity was increased from the 2-on-1 to the 3-on-2 situation. In Study 2, 58 rugby league players undertook the dual-task draw-and-pass assessment. Players then competed in National Rugby League matches with video footage coded for the number of tries scored and the activities that led to the try. A total of 303 tries were scored with 150 (49.5%) tries scored from a draw-and-pass situation. Significant associations were detected between 2-on-1 dual-task draw-and-pass performance in the isolated test condition and draw-and-pass performances in competition. These studies provide evidence of (i) the greater attentional demands of the skill of drawing-and-passing in elite team sport athletes when more players are involved and (ii) the practical utility of off-field dual-task testing in supplying information predictive of skills performance in competition.